The Transformation of Communication Medium among Sulinggih in the Development of Technology - Dewi, Ida Ayu Made Ratih Praba (Bali Tourism Board, 2024)
In its history, religious education was delivered by Sulinggih as religious leaders through oral traditions. However, the development of technology and communication has brought significant changes to various aspects of life, including how religious material is conveyed. This transformation presents both opportunities and challenges in ensuring that religious teachings remain relevant, engaging, and accessible to the modern generation. This article discusses how technological advancements have altered the communication approach of Hindu religious leaders in spreading religious knowledge to society. Using qualitative research, data is presented in the form of narrative descriptions based on the Shannon-Weaver Communication model. Data collection techniques include observation and literature study. The author conducted an observation of a video upload on the Wira.ID Channel YouTube channel, which featured dharma wacana (discourse) by a sulinggih. Meanwhile, the literature study was drawn from books and scientific journals with similar themes. Based on data analysis, it was found that Sulinggih can now utilize social media to expand the reach of their messages and create more inclusive communication. Digital platforms allow the spread of Hindu religious knowledge not only in physical spaces but also to a broader audience, including the younger generation. Despite challenges such as video quality issues and internet connection disruptions, the use of YouTube offers significant advantages in disseminating religious information. Hindu religious leaders' adaptation to this technology is also reflected in the application of interpersonal communication principles, creating a familiar and comfortable atmosphere between the communicator and the audience. By using YouTube, sulinggih can reduce potential redundancy and entropy in communication, ensuring the message remains clear. The large capacity of YouTube channels enables broadcasting to a large number of viewers, supporting the use of this media in spreading Hindu teachings in a more dynamic and relevant way to meet the needs of the times.